The Comparasion of Economic Productivity of Gillnets used in the Keban Dam Lake - Dartay, Mürşide; Ateşşahin, Tuncay (Fırat University, 2016)
This study was carried out between July 2012 and March 2013. The economic productivity of multimonofilament and multifilament gillnetswhich used in research area were comparated. In the study,eighteen catch operation were carried out. A total of caught 247,191 kg fishes. The totalamount of fishcaughtwith the multimonofilamentgillnetwas calculated as138,848 kg (800 meter), andderived income 367,32. The totalamount of fishcaughtwith the multifilament gillnet was calculated as 108,343 (800 metre), andderived income278,825 .According to obtained data, calculations were performed for catch operations in the one fishing season (180 catch operation / 1 fishing season). As a result; multi-monofilament gillnets were six times more productivity than multifilament gillnets

Bu çalışma, Temmuz 2012- Mart 2013 tarihleri arasında gerçekleştirildi. Bölgede yaygın olarak kullanılan multimonofilament ve multifilament galsama ağlarının ekonomik verimlilikleri karşılaştırıldı. Çalışmada 18 avcılık operasyonu sonucunda toplamda 247,191 kg balık avlandı. Multi-monofilament ağlarla avlanan balık miktarı 138,848 kg, elde edilen toplam gelir; 367,32 olmaktadır. Multifilament ağlarla avlanan balık miktarı 108,343 kg, elde edilen gelir; 278,825 olarak tespit edildi. Elde edilen bu veriler ışığında, ekonomik verimlilik hesaplamaları, balıkçıların bir avlama sezonunda yaptığı avcılık operasyonuna göre yapıldı (180 avcılık operasyonu /1 avlama sezonu). Sonuç olarak; multi-monofilament ağların getirisinin multifilament ağlardan 6 kat daha fazla olduğu tespit edildi
Keban Baraj Gölünde Kullanılan Galsama Ağlarının Ekonomik Verimliliklerinin Karşılaştırılması